Protective potential of BM-MSC extracted Exosomes in a rat model of Alzheimer’s disease - Atefeh Sadeghi; Maryam Noorbakhshnia; Shabanali Khodashenas (PLoS ONE, 2025)
Exosomes are extracellular vesicles, which are released into the extracellular space by all types of cells, especially stem cells. Compared with stem cells, exosomes are safer and can be considered one of the most promising therapeutic strategies for neurodegenerative disease. We examined the effect of exosomes derived from bone marrow mesenchymal stem cells (BM-MSC) on a rat model of Alzheimer’s disease (AD). For this purpose, male Wistar rats weighing 220–250 g were used. For the induction of AD, rats received a daily dosage of 100 mg/kg Aluminum chloride (Alcl3) by oral gavage for 60 days. Also, Primary BM-MSC was extracted from the femora of Wistar rats (male, 100–150 g). Extracted exosomes were Characterized and Qualified using TEM Microscope and Zetasizer Nano. Specific markers of exosomes were evaluated by Flow cytometry. MSC-extracted exosomes (150 µg/µl) were injected 2 or 5 times into the animals via tail vein on specific days. Our data revealed that receiving exosomes significantly prevented AlCl3-induced enhancement of hippocampal APP gene expression, beta-amyloid plaque formation, impairment of passive avoidance learning and spatial memory. However, exosome injections in healthy subjects caused some negative effects such as spatial memory impairment. It seems, MSC-derived exosomes can be considered as a candidate to prevent AD progression.